2013
DOI: 10.1371/journal.pone.0067210
|View full text |Cite
|
Sign up to set email alerts
|

Context-Dependent Competition in a Model Gut Bacterial Community

Abstract: Understanding the ecological processes that generate complex community structures may provide insight into the establishment and maintenance of a normal microbial community in the human gastrointestinal tract, yet very little is known about how biotic interactions influence community dynamics in this system. Here, we use natural strains of Escherichia coli and a simplified model microbiota to demonstrate that the colonization process on the strain level can be context dependent, in the sense that the outcome o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 61 publications
(68 reference statements)
0
24
0
Order By: Relevance
“…Many host-specific factors have been studied, including host species, genotype, diet and health (Rawls et al, 2006;Turnbaugh et al, 2006;Benson et al, 2010;Goodrich et al, 2014), as well as microbe-specific factors, including mutualistic and competitive interactions (de Muinck et al, 2013;Levy and Borenstein, 2013). While the list of potential factors is long, they can be divided into two major categories: selective processes, in which microbes establish and thrive in an environment (in this case the host itself) due to differences in their relative ecological fitness; and neutral processes, which include the dynamics of passive dispersal (for example, sampling individuals from a source pool of available colonists) and the effects of ecological drift (the stochastic loss and replacement of individuals; Chase and Myers, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Many host-specific factors have been studied, including host species, genotype, diet and health (Rawls et al, 2006;Turnbaugh et al, 2006;Benson et al, 2010;Goodrich et al, 2014), as well as microbe-specific factors, including mutualistic and competitive interactions (de Muinck et al, 2013;Levy and Borenstein, 2013). While the list of potential factors is long, they can be divided into two major categories: selective processes, in which microbes establish and thrive in an environment (in this case the host itself) due to differences in their relative ecological fitness; and neutral processes, which include the dynamics of passive dispersal (for example, sampling individuals from a source pool of available colonists) and the effects of ecological drift (the stochastic loss and replacement of individuals; Chase and Myers, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…and interactions between all of these actors. Interactions between microorganisms are beginning to be depicted through predatorprey models [5] and/or context-dependent competition [6] . Co-evolution of microorganisms and host provide a beneficial symbiotic relationship; thus, besides the biotic interactions that influence community dynamics, symbiotic events occur between microorganisms and host determinants shaping the microbial community as well as the local conditions [7,8] .…”
Section: From Gut Ecosystem To Dysbiosismentioning
confidence: 99%
“…In vitro studies of GI bacteria have even shown that strain-level dynamics can be determined by interactions with very distantly related taxa (de Muinck et al, 2013). This suggests that the dynamics can be modulated by biotic interactions across taxonomic levels.…”
Section: Box 1 Taxonomic Scale Of Observationmentioning
confidence: 99%
“…In the case of the GI microbiota, this is, in general, not a viable option as most species are non-cultivable (Zoetendal et al, 2004). Also, the form of a pairwise interaction may depend upon the environmental context in which it takes place (de Muinck et al, 2013), making extrapolation from laboratory experiments to natural systems problematic.…”
Section: Introductionmentioning
confidence: 99%